Concepções de natureza na filosofia: contribuições à educação ambiental - Andrade, Mariana Nayara Bonilha de (2019)
Understanding the complexity of the construction of a concept and its different implications in the historical and daily production of the culture of a society, in the present work we aim to study the concept of Nature in the light of History and Philosophy as fundamental theoretical contributions to understand Environmental Education in its multiplicity. The objective, in this work, is to discuss how nature serves the modes of production as regards the way of living and conceiving of nature and its relation to Man. For this, we approach different doctrines elaborated in the historical and philosophical course, starting from the ideal Rationalism of Ancient Greece to the Positivism of Modernity. It is a qualitative, exploratory research based on the assumption that learning is best performed when part of the known, always seeking to broaden the horizons of knowledge through readings and studies on the subject that generate rational answers. Thus, this dissertation will be organized into three chapters: 1º Nature; 2º The Environmental Education Trends; and 3º The Dialogue between conceptions of Nature and Environmental Education. This text is an invitation to rethink the vision of nature, the concept of environment, Environmental Education and reflect critically on the Man-Nature relationship; denaturing obvious and raising new questions that may inspire actions and research.